Mechanistic insights into high mobility group box-1 (HMGb1)-induced Toll-like receptor 4 (TLR4) dimer formation. Issue 14 (22nd September 2019) - Sun, Shan; He, Mingzhu; VanPatten, Sonya; Al-Abed, Yousef
Abstract: Supplemental data for this article can be accessed here.High mobility group box-1 (HMGb1), an endogenous danger-associated molecular pattern protein (DAMP) whose extracellular release has been associated with sterile injury and various inflammatory diseases and conditions, has been shown to be a valuable clinical drug target. Elucidation of the specific interactions with the HMGb1 receptor, Toll-like receptor 4 (TLR4) and adaptor protein myeloid differentiation factor-2 (MD-2), will lead to more precisely targeted therapeutics. We sought to examine detailed interactions and dynamics of the HMGb1 A-box and B-box fragments, as well as the intact protein using in silico protein–protein docking (ZDOCK, ZRANK) and molecular dynamics (Schrödinger Desmond, New York, NY). Mutagenesis and SPR-binding studies allowed us to draw further conclusions regarding the details of the HMGb1–TLR4–MD2 interaction and shed light on the reasons for the opposing biological activities of HMGb1 A-box and B-box fragments. From our findings, we hypothesize that disulfide A-box fragment binds as an anchor toward the TLR4–MD-2 but does not facilitate the TLR4 dimer formation, thereby competing with the HMGb1-binding site and preventing HMGb1-induced signaling and downstream inflammation, whereas the pro-inflammatory B-box fragment retains the MD-2 active conformation and binds to both TLR4 proteins in the complex to aid TLR4 dimer formation, which activates the intracellular signaling for downstream inflammatory pathways and cytokine release. Communicated by Ramaswamy H. Sarma